Extreme Curvature of Shallow Magma Pathways Controlled by Competing Stresses: Insights From the 2018 Sierra Negra Eruption. Issue 13 (6th July 2021) - Davis, Timothy; Bagnardi, Marco; Lundgren, Paul; Rivalta, Eleonora
Abstract: Eruptions at shield volcanoes often occur from radially aligned linear fissures fed by blade‐like magma‐filled cracks (dykes). The fissures of the 2018 Sierra Negra eruption were scattered on the flank of the volcano. Space‐borne radar interferometric data (interferometric synthetic aperture radar) revealed that, unexpectedly, part of the eruption was fed by a 15 km long, tortuous and flat‐lying crack (sill). Here we develop a framework that captures the full three‐dimensional (3D) kinematics of non‐planar intrusions. This includes both an analytical and comprehensive numerical scheme. We constrain the models such that they match the observed ground deformation at Sierra Negra. We show that the peculiar sill trajectory is due to the competing stress gradient magnitudes being close to one another throughout its propagation. By accounting for the interaction of all these factors, these 3D models open the possibility to understand and simulate the geometry of magma transport at volcanic systems. Plain Language Summary: Here, we show in unprecedented detail using space‐borne radar interferometric data, a large volume eruption at Sierra Negra volcano, Galápagos Islands fed by a flat‐lying crack (sill). The observations are particularly intriguing as this sill's trajectory was over 15‐km‐long and while it remained flat it was highly curved, which, cannot be explained by existing models. We employ simple fracture mechanics models to show that the sill grew away from the summit due to the stresses induced by the slope of the volcano. Further from the summit, forces caused by the magma/rock weight contrast began to compete with the slope stresses causing the sill's growth direction to turn as observed. We show how parameters such as: magma volume, weight contrast, sill depth and the tectonic stresses, play a role in defining if/where the flank eruption occurs. To summarize, we show a well constrained example of a curved sill‐fed eruption, which has never been observed in such detail before. These observations warranted the use of new three‐dimensional (3D) models to help explain the process. This work shows how to analyze the paths of cracks feeding volcanic flank eruptions efficiently in 3D, and can be used to understand the potential hazard of a particular batch of magma. Key Points: The 2018 eruption at Sierra Negra volcano, Galápagos Islands, was fed by a highly curved sill The curvature of the sill's trajectory was due to competing stresses: topographic loading, weight contrasts, and free surface effects Shallow flat‐lying intrusions are unstable and as such are extremely likely to turn at a given distance from the edifice's center